Oxidized human serum albumin as a possible correlation factor for atherosclerosis in a rural Japanese population: the results of the Yakumo Study - Ryosuke Fujii; Jun Ueyama; Arisa Aoi; Naohiro Ichino; Keisuke Osakabe; Keiko Sugimoto; Koji Suzuki; Nobuyuki Hamajima; Kenji Wakai; Takaaki Kondo (Komiyama Printing Co. Ltd, 2018)
Abstract Background The effect of the redox state of human serum albumin (HSA) on the antioxidant properties of the entire body has been a focus of recent research. The usefulness of HSA redox state as a biomarker for reducing oxidative stress has been investigated in clinical settings; however, evidence for its significance as a health index in non-clinical settings is yet to be established. This study aimed to examine the associations between HSA redox state and the atherosclerotic indices of carotid intima-media thickness (IMT) and plaque formation in a rural Japanese population. Methods We conducted a cross-sectional study as part of a health check-up program in the rural area of Hokkaido, Japan, at the end of August 2013. A total of 281 residents (124 men and 157 women) were included in the final analysis. Lifestyle-related data were obtained through a self-reported questionnaire, and ultrasound examinations were performed to measure IMT and determine plaque formation. The high-performance liquid chromatography postcolumn bromocresol green method was used to separate HSA into human nonmercaptalbumin and human mercaptalbumin (HMA). Results We found a significant negative relationship between the fraction of HMA [f(HMA)] and IMT (standardized β = − 0.132, p = 0.03). Moreover, f(HMA) was significantly associated with plaque formation (p < 0.01) with an odds ratio of 0.89 (95% confidence interval, 0.81-0.97) for every 10% increment in f(HMA). Conclusions We found that the HSA redox state, as determined by f(HMA), was associated with atherosclerotic indices in Japanese subjects. These results suggest that the HSA redox state indicates the risk of developing atherosclerosis.